Impact of PM2,5 Particulate Matter on Air Quality Due to the Burning of Saccharum officinarum in Laredo, Trujillo-Peru (SCIÉNDO INGENIUM, 2025)
This study analyzes the impact of PM2.5 particulate matter generated by the burning of Saccharum officinarum hectares in Laredo between 2017 and 2022. Meteorological data were obtained using the WRF model with a 1 km resolution, covering Trujillo and the Pacific Ocean. The WRF results were validated through comparison with observed data, showing high correlation and predictive capability. The dispersion of PM2.5 was simulated using the Calpuff model from the Environmental Protection Agency (EPA), validated with data from controlled burns and various burning scenarios. The analyses showed maximum PM2.5 concentrations in areas near emission sources, exceeding Environmental Quality Standards (EQS). This was particularly evident between June and November due to south-southeast winds and subsidence inversion conditions. In 2021, critical days exhibited calm wind conditions. Regarding emissions, the burning of 3 hectares generated a moderate air quality index for 60.47% of the receptors. In contrast, the burning of 6 and 9 hectares reached the caution threshold, affecting 32.56% and 43.41% of the receptors, respectively.
Keywords: Sugarcane burning; PM2,5 particulate matter; sugarcane; WRF; modeling; Calpuff